KAJIAN PERSEBARAN dan POTENSI JATI PASIR (Guettarda speciosa L.) di INDONESIA - Astuti, Inggit Puji; Susandarini, Ratna (BERITA BIOLOGI, 2019)
Rubiaceae is a cosmopolitan family of flowering plants distributed at almost all over the world. This family consists of 611 genera and 13,500 species. One of the 611 genera is Guettarda that has 50 to 160 species. Guettarda speciosa L. is one of species within Guettarda which is distributed from East Africa to the Pacific Islands including Indonesia. The objective of this study, therefore, was to determine the species’ distribution in Indonesia and its potential use. The data was collected from herbarium specimens deposited in Herbarium Bogoriense, field collection data from exploration by Center for Plant Conservation, Indonesian Institute of Sciences, and NKRI Expedition in West Papua. Based on the collected data, an analysis was conducted to create distribution map of the species. Information related to the potential use of this species in Indonesia showed thatit iscommonly used as ornamental plant, although Rumphius reported that in Ambon the wood or bark of this species was usually boiled together with root ofArtocarpus as a traditional medicine for diarrhea.